2001
DOI: 10.1111/j.1748-0361.2001.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Diabetic Retinopathy in Rural Areas: The Potential of Telemedicine

Abstract: Diabetic retinopathy is a common cause of blindness, and screening can identify the disease at an earlier, more treatable stage. However, rural individuals with diabetes may have limited access to needed eye care. The objective of this project was to demonstrate the feasibility of a diabetic retinopathy screening program using a state-of-the-art nonmydriatic digital fundus imaging system. The study involved a series of patients screened in primary care and public health locations throughout seven predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Although most of the published works have been descriptive in nature, there have been some comparative trials that compared images from video fundus cameras to 35 mm film in detection of diabetic retinopathy. [7][8][9][10] The results so far have been encouraging. Relatively little work has been done on anterior segment telemedical examinations.…”
Section: Introductionmentioning
confidence: 60%
“…Although most of the published works have been descriptive in nature, there have been some comparative trials that compared images from video fundus cameras to 35 mm film in detection of diabetic retinopathy. [7][8][9][10] The results so far have been encouraging. Relatively little work has been done on anterior segment telemedical examinations.…”
Section: Introductionmentioning
confidence: 60%
“…The prevalence of diabetic retinopathy being diagnosed with nFP was similar to those reported by the Centers for Disease Control and Prevention recently, 1 but lower in both our study populations (rural and urban) compared with reports from several years ago. 3 Cummings et al 29 found the prevalence of diabetic retinopathy in a rural eastern North Carolina community to be as high as 40.9% among their study patients, much higher than our rural cohort. A similarly high incidence was reported by Murgatroyd et al 21 These observations may highlight possible regional differences among rural and urban communities even within the United States, or they may also highlight a possible recent trend toward a decrease in incidence of retinopathy with improved glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Nonmydriatic 45°cameras have also been developed. Initially used in epidemiologic studies [7][8][9] and later in telemedicine applications, [10][11][12][13] nonmydriatic cameras are increasingly accepted in clinical practice. Attractive features include infrared illumination more comfortable to patients, special alignment guides, automatic focus, and programmable internal fixation target positions.…”
mentioning
confidence: 99%